Determinants of Employee Performance in Public Sector Organizations: The Role of Workload, Incentives, and Leadership Style - Indah Safriani Putri; Hasniaty; Nasir Hamzah (Yayasan Amerta Insan Unggul, 2026)
This study examines the influence of workload, incentives, and leadership style on employee performance in a public sector organization, specifically at the Class I TPI Immigration Office Makassar. Despite extensive research on employee performance, empirical evidence integrating these variables simultaneously within public service institutions remains limited. This study adopts a quantitative approach using a census sampling technique involving 116 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression with IBM SPSS. The findings reveal that workload has a significant negative effect on employee performance, indicating that excessive job demands reduce productivity and effectiveness. In contrast, incentives and leadership style demonstrate significant positive effects, suggesting that fair compensation systems and adaptive leadership practices enhance employee motivation and performance outcomes. Among the variables, incentives emerge as the most dominant factor, followed by leadership style, while workload contributes negatively. Simultaneously, all independent variables significantly influence employee performance, with the model explaining 85% of the variance. These results highlight the importance of balanced workload management, equitable incentive systems, and effective leadership in improving organizational performance. The study contributes to the human resource management literature by providing empirical evidence from a public sector context and offering a comprehensive framework that integrates workload, incentives, and leadership style. Practically, the findings provide strategic insights for policymakers and organizational leaders to enhance employee performance and public service quality.